Intracystic pressure in patients with temporal arachnoid cysts: a prospective study of preoperative complaints and postoperative outcome. Issue 6 (8th December 2006) - Helland, Christian A; Wester, Knut
Abstract : Background: Arachnoid cysts (AC) can cause a wide spectrum of clinical symptoms. Only a limited number of studies have investigated intracranial pressure in patients with AC. We wished to investigate the relationship between intracystic pressure, preoperative complaints and postoperative symptom relief in adult patients operated on for a unilateral temporal AC. Material and methods: This was a prospective, population based study involving 38 adult (>18 years) patients (mean age 43 years; range 18–69) with a previously untreated unilateral temporal AC. Results: For all cyst types, mean pressure was 131 mm H2 O. The main preoperative complaints were headache and dizziness/nausea. By median split, patients were divided into a low pressure (<130 mm H2 O) and a high pressure (>130 mm H2 O) group. Patients with high intracystic pressure had a significantly higher preoperative visual analogue scale (VAS) score (54.7) than that found in patients with low intracystic pressure (39.4). Both pressure groups had a significant fall in VAS score after surgical decompression of the cyst. Intracystic pressure correlated significantly with arterial pCO2 and mean arterial pressure. Conclusion: There was a significant correlation between intracystic pressure and the preoperative level of complaints. Mean intracystic pressure in adult patients with unilateral temporal AC seems to lie within the limits of normal intracranial pressure. We therefore hypothesise that factors other than absolute pressure, such as altered compliance and impedance of the brain, may be involved in the pathophysiology of intracranial AC.